Protein for a Healthy Future: How to Increase Protein Intake in an Environmentally Sustainable Way in Older Adults in the Netherlands - Grasso, Alessandra C (J Nutr, 2020)
BACKGROUND: Protein intake greater than the currently recommended amount is suggested to improve physical functioning and well-being in older adults, yet it is likely to increase diet-associated greenhouse gas emissions (GHGEs) if environmental sustainability is not considered. OBJECTIVES: We aimed to identify dietary changes needed to increase protein intake while improving diet environmental sustainability in older adults. METHODS: Starting from the habitual diet of 1,354 Dutch older adults (aged 56–101 y) from the Longitudinal Aging Study Amsterdam cohort, mathematical diet optimization was used to model high-protein diets with minimized departure from habitual intake in cumulative steps. First, a high-protein diet defined as that providing ≥1.2 g protein · kg body weight(−1) · d(−1) was developed isocalorically while maintaining or improving nutritional adequacy of the diet. Second, adherence to the Dutch food-based dietary guidelines (FBDG) was imposed. Third, a stepwise 10% GHGE reduction was applied. RESULTS: Achieving a high-protein diet aligned with the FBDG without considering GHGEs required an increase in vegetables, legumes, nuts, whole grains, meat/dairy alternatives, dairy, and eggs and a reduction in total meat (for men only) and discretionary products, but it resulted in a 5% increase in GHGEs in men and 9% increase in women. When a stepwise GHGE reduction was additionally applied, increases in poultry and pork (mainly for women) and decreases in beef/lamb and processed meat were accrued, with total meat staying constant until a 50–60% GHGE reduction. Increases in whole grains, nuts, and meat/dairy alternatives and decreases in discretionary products were needed to lower GHGEs. CONCLUSIONS: A high-protein diet aligned with FBDG can be achieved in concert with reductions in GHGEs in Dutch older adults by consuming no more than the recommended 500 g meat per week while replacing beef and lamb and processed meat with poultry and pork and increasing intake of diverse plant-protein sources.